EVALUASI PENGALAMAN PENGGUNA CLOUD-PMS SYSTEM GUESTPRO MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE PLUS - Vitanandhini, Ni Kadek Aurelia; Paramitha, A.A. Istri Ita; Putri, I Gusti Agung Pramesti Dwi (Politeknik Bisnis Indonesia, 2024)
The Cloud-PMS system is a cloud-based solution within GuestPro designed to simplify key operational processes in the hospitality industry. However, the results of system observations show that users face various obstacles caused by regular feature updates, especially for users who are not familiar with the system. As a result, the efficiency and effectiveness of user satisfaction decreases. This study aims to evaluate User Experience on the Cloud-PMS system to measure user perception and experience using the User Experience Questionnaire Plus (UEQ+) method which is an extension of the UEQ method. And with this method, the researcher measured 15 out of a total of 27 existing scales. The Proportionate Stratified Random Sampling technique was used in sampling, involving 172 respondents. The results of the study show that users prioritize the functional aspect more than visual aesthetics. However, overall evaluation of the system tends to give more positive results than negative. These findings highlight the relevance of the 15 scales measured in evaluating the usability of the system and show that it has met user expectations in terms of functionality. This research emphasizes the importance of integration between functional and aesthetic aspects in the development of hotel management systems.